INCIDENCE OF DILATED CARDIOMYOPATHY IN PATIENTS OF THALASSEMIA MAJOR RECEIVING DEFERASIROX AND DEFEROXAMINE AS CHELATORS - MUSTAFA , A; NADEEM , MT; KHAN , SA; ZAHID , J; ZAFAR , A; WAHEED , M (Biological and Clinical Sciences Research Journal, 2023)
The objective of this study was to determine the frequency of dilated cardiomyopathy in patients with β-thalassemia major who received treatment with deferasirox and deferoxamine. A descriptive cross-sectional study was conducted in the Department of Paediatrics, Combined Military Hospital, Rawalpindi, from May 2022 to January 2023. All 746 paediatric patients aged between 4 to 18 years, of both genders, who had been diagnosed with β-thalassemia major and had received chelation with either deferasirox or deferoxamine for at least one continuous year were included. Patients who were non-compliant with treatment based on history or suffered from concurrent chronic cardiopulmonary, renal (including proteinuria), hepatic, or neoplastic disease, those who suffered from malabsorption syndromes, or those who had undergone gastrointestinal surgery were excluded. All patients underwent a 2D echocardiographic study to document cardiac dilatation and measurement of ejection fraction. Dilated cardiomyopathy was defined as dilating one or both heart ventricles with an ejection fraction of less than 40%. Patients were divided into two groups: those who had received deferasirox and those who had received deferoxamine. Data was analyzed using SPSS 26.0. The study population had a median age of 8.00 (IQR: 5.00) years, with a male majority of 384 (51.5%). The median time on chelation therapy was 23.00 (IQR: 10.00) months, while the median age at first transfusion was 12.00 (IQR: 7.00) months. The median number of lifetime transfusions was 60.50 (IQR: 33.00), while only 431 (57.8%) patients had received chelator therapy previously. Out of the total sample population, 36 (4.8%) patients had dilated cardiomyopathy, of whom 22 (5.9%) occurred with deferasirox while 14 (3.8%) were seen with deferoxamine (p=0.172). The study concluded that the frequency of dilated cardiomyopathy secondary to iron deposition in the myocardium of patients with β-thalassemia major on deferasirox for at least one year was similar to those using deferoxamine for the same minimum period.